Effect of dilute H on crack tip plasticity in Zr - Ruda, Margarita María (2013)
We studied the plasticity mechanisms that occur near a crack tip in hcp Zr with dilute amounts of interstitial H impurities. A quasi-static method was used to simulate crack propagation and the atomic interactions were described by the embedded-atom (EAM) type potentials. We analyzed the influence of H atoms on the deformation mechanisms and phase transformations taking place near the crack tip loaded in Mode I. Crack advance was monitored as a function of the applied stress intensity and it was found to depend on the geometry and orientation of the crack and on the specific position of the H interstitials. As in pure Zr, twinning, dislocations, hcp to fcc and hcp to bcc martensitic transformations near the crack tip are competing deformation mechanisms. Dilute amounts of interstitial H in the crack tip region significantly affect this competition. The results indicate that for most orientations the presence of dilute H interstitials leads to an increase in ductility.